Struktur Komunitas Bivalvia pada Ekosistem Lamun di Pantai Tukak Kabupaten Bangka Selatan - Rozas; Hudatwi, Mu’alimah; Syari, Indra Ambalika (Jurnal Ilmu Kelautan Lesser Sunda, 2022)
Bivalves are one of the aquatic biotas that have important economic value and have a fairly high nutritional content role in the waters. The high ecomonic value of bivalves can lead to over exploitation, resulting in reduced productivity and impact on the sustainability of bivalves in seagrass ecosystems. Bivalves are a class of mollusk phylum associated with seagrass ecosystem and have an important role in water. Based on this, it is necessary to conduct recearch related to the structure of the bivalves community in seagrass ecosystems. This research was conducted in Mei 2021 at Tukak Beach South Bangka Regency. Seagrass data were collected using a 50x50 cm² quadrant transect and a distance of 50 m and a distance between transects of 5 m, while bivalves data were taken according to the seagrass transect. Data retrieval is divided into 3 stations, where each station consisting of 3 sub-stations. Where each stasion consists of sub stations. The results obtained 4 species of seagrass and 10 spescies of bivalves from families. Bivalves density value of 8,67-30,67 ind/m². diversity index 1,88-2,33, uniformity index 0,73-0,85, and dominance index 0,29-0,35. Based on principal component analysis (PCA) it was found that the density of bivalves was positively correlated with pH, brightneess, and DO. While the results of the correlation factorial analysis (CA) that there were 3 groups that had a close relationship between the density of seagrass and the density and the bivalves.